Disentangling ecological drivers of interspecific achromatic plumage variation in birds - Su Wu; Kai Zhang; Bin Wang; Pinjia Que; Biao Yang; Yu Xu (Global Ecology and Biogeography, 2024)
Aim Understanding the ecological determinants of interspecific achromatic (light‐to‐dark) plumage variation in birds is crucial yet challenging due to the complex interplay of climatic, habitat‐related, and morphological influences. This study aimed to disentangle the effects of temperature, precipitation, habitat openness, body mass and hand‐wing index (HWI, a widely used single‐parameter proxy for the extent to which a species relies on flight) on shaping achromatic plumage variation among bird species. Location Global. Time Period Contemporary. Major Taxa Studied Birds. Methods Based on data from over 8000 sessile bird species globally, we employed phylogenetic linear regressions to account for achromatic plumage colour in relation to temperature, precipitation, habitat openness, body mass and HWI, while correcting for phylogenetic non‐independence between species. Furthermore, we conducted phylogenetic path analyses to decompose direct from indirect effects. Results We found that temperature, precipitation, habitat openness and body mass exerted separate but interactive effects on the variation in achromatic colour across species. Species inhabiting cold, wet or densely vegetated environments were darker coloured, while smaller species were lighter. Darker plumage was more strongly related to higher precipitation in colder regions for nocturnal species. For diurnal species, darker plumage was more closely associated with higher precipitation in more open habitats, whereas lighter plumage was more linked to lower mass in denser habitats. Noteworthy was the identification of a substantial correlation between achromatic colour and HWI. Diurnal species that are more aerial were lighter. Conversely, nocturnal flyers, especially females, tended to be darker. Main Conclusions The findings highlight the multifaceted nature of plumage coloration evolution, with adaptations for thermal efficiency, crypsis, signalling, waterproofing or protection against bacteria. However, the variable relative importance of these factors among groups emphasizes the significance of each factor in different contexts.

Sex differences in immune gene expression in the brain of a small shorebird - José O. Valdebenito; Kathryn H. Maher; Gergely Zachár; Qin Huang; Zhengwang Zhang; Larry J. Young; Tamás Székely; Pinjia Que; Yang Liu; Araxi O. Urrutia (Immunogenetics, 2022)
Males and females often exhibit differences in behaviour, life histories, and ecology, many of which are typically reflected in their brains. Neuronal protection and maintenance include complex processes led by the microglia, which also interacts with metabolites such as hormones or immune components. Despite increasing interest in sex-specific brain function in laboratory animals, the significance of sex-specific immune activation in the brain of wild animals along with the variables that could affect it is widely lacking. Here, we use the Kentish plover ( Charadrius alexandrinus ) to study sex differences in expression of immune genes in the brain of adult males and females, in two wild populations breeding in contrasting habitats: a coastal sea-level population and a high-altitude inland population in China. Our analysis yielded 379 genes associated with immune function. We show a significant male-biased immune gene upregulation. Immune gene expression in the brain did not differ in upregulation between the coastal and inland populations. We discuss the role of dosage compensation in our findings and their evolutionary significance mediated by sex-specific survival and neuronal deterioration. Similar expression profiles in the coastal and inland populations suggest comparable genetic control by the microglia and possible similarities in pathogen pressures between habitats. We call for further studies on gene expression of males and females in wild population to understand the implications of immune function for life-histories and demography in natural systems.

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

Offspring sex ratio is unrelated to parental quality and time of breeding in a multiple-breeding shorebird - Pinjia Que; Tamás Székely; Pengcheng Wang; Qi Lu; Weipan Lei; Yang Liu; Zhengwang Zhang (Journal of Ornithology, 2019)

Parental cooperation in a changing climate: fluctuating environments predict shifts in care division - Orsolya Vincze; András Kosztolányi; Zoltán Barta; Clemens Küpper; Monif Alrashidi; Juan A. Amat; Araceli Argüelles Ticó; Fiona Burns; John Cavitt; Warren C. Conway; Medardo Cruz‐López; Atahualpa Eduardo Desucre‐Medrano; et al. (Global Ecology and Biogeography, 2017)
Aim Parental care improves the survival of offspring and therefore has a major impact on reproductive success. It is increasingly recognized that coordinated biparental care is necessary to ensure the survival of offspring in hostile environments, but little is known about the influence of environmental fluctuations on parental cooperation. Assessing the impacts of environmental stochasticity, however, is essential for understanding how populations will respond to climate change and the associated increasing frequencies of extreme weather events. Here we investigate the influence of environmental stochasticity on biparental incubation in a cosmopolitan ground‐nesting avian genus. Location Global. Methods We assembled data on biparental care in 36 plover populations ( Charadrius spp.) from six continents, collected between 1981 and 2012. Using a space‐for‐time approach we investigate how average temperature, temperature stochasticity (i.e. year‐to‐year variation) and seasonal temperature variation during the breeding season influence parental cooperation during incubation. Results We show that both average ambient temperature and its fluctuations influence parental cooperation during incubation. Male care relative to female care increases with both mean ambient temperature and temperature stochasticity. Local climatic conditions explain within‐species population differences in parental cooperation, probably reflecting phenotypic plasticity of behaviour. Main conclusions The degree of flexibility in parental cooperation is likely to mediate the impacts of climate change on the demography and reproductive behaviour of wild animal populations.

Low nest survival of a breeding shorebird in Bohai Bay, China - Pinjia Que; Yajing Chang; Luke Eberhart-Phillips; Yang Liu; Tamás Székely; Zhengwang Zhang (Journal of Ornithology, 2015)